Psikoedukasi Skizofrenia Melalui Siaran Radio Di Komunitas Peduli Skizofrenia Indonesia Jakarta - Fadhilatul Janah; Sokhivah Sokhivah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The stigma against schizophrenia is still a major challenge in efforts to increase public understanding and support for individuals who experience this disorder. Psychoeducation through mass media, such as radio broadcasts, has been proven effective in reducing stigma and increasing knowledge about schizophrenia. Psychoeducational outreach through radio mass media is an effective strategy to increase public understanding about schizophrenia. This research aims to explore the potential of radio as a means of disseminating accurate and educational information about schizophrenia. The research methods used were interviews with psychiatric experts and radio producers, as well as content analysis of existing radio programs. Findings suggest that through a creative and structured approach, radio can be an effective platform for conveying information about symptoms, treatment, and support to individuals experiencing schizophrenia and their families. Psychoeducational outreach via radio can play an important role in reducing stigma, increasing awareness, and promoting social support for individuals with schizophrenia.